Neuroinflammation in Pulmonary Hypertension: Concept, Facts, and Relevance - Hilzendeger, Aline M. (Springer US, 2014)
Pulmonary hypertension (PH) is a progressive lung disease characterized by elevated pressure in the lung vasculature, resulting in right-sided heart failure and premature death. The pathogenesis of PH is complex and multifactorial, involving a dysregulated autonomic nervous system and immune response. Inflammatory mechanisms have been linked to the development and progression of PH; however, these are usually restricted to systemic and/or local lung tissue. Inflammation within the CNS, often referred to as neuroinflammation involves activation of the microglia, the innate immune cells that are found specifically in the brain and spinal cord. Microglial activation results in the release of several cytokines and chemokines that trigger neuroinflammation, and has been implicated in the pathogenesis of several disease conditions such as Alzheimer’s, Parkinson’s, hypertension, atherosclerosis, and metabolic disorders. In this review, we introduce the concept of neuroinflammation in the context of PH, and discuss possible strategies that could be developed for PH therapy based on this concept.